Organização e desenvolvimento do estágio curricular na formação de professores de biologia - Lisovski, Lisandra Almeida (2006)
Understanding the complexity of the organization and the development of School training does not seem to be something to be postponed. This research aims to point out contributions to Universities and Elementary Education Schools in order to put up shared practices among the institutions concerning planning, accompaniment and evaluation of school training. This research aimed to find answers to the following problem: Which aspects are relevant to characterize the organization and the development of school training in the Biology Courses from Universidade Regional Integrada do Alto Uruguai e das Missões URI Erechim Campus and Universidade Federal de Santa Maria (UFSM). This is a qualitative research that involved the two institutions quoted above and 35 EEB (13 from Erechim and 22 from Santa Maria). As research sources, information from documents that direct the development of school training in the universities and the EEB were used, as well as 89 people who built the real sample of the research: 24 Biology teachers (12 from Erechim EEB and 12 from Santa Maria); 17 members of the board of the EEB from Erechim; 4 school training advisors (2 from URI and 2 from UFSM) and 44 school trainees (24 from URI and 24 from UFSM). Questionnaires, interviews and document analysis were the instruments for data collection. Although the research was carried out in two different towns the answers were similar. These answers show that the problems and difficulties faced in the process of organization and development of school training are not specific of one single teaching institution, but they happen in several institutions. Among the results of the research we can highlight: the students are educated for school training through the disciplines; the school training follow the legislation; the courses under study have some lines that govern the development of school training; the accompaniment of the trainees is done by the advisors, with individual and group attendance to grant the continuity of the frequency. The EEB do not have lines to orient the development of school trainings; the members of the board team almost never accompany the school trainings and there are few biology teachers who do that, most of the teachers just see the class plans made by the students; the responsibility of the EEB is limited to dispose classes for the school training; most of the EEB teachers think that the trainees should know better the reality of the school, should have a better knowledge of the content, and should take over the class, that is, students should have experience. We can say that there few institutionalized forms of interaction between the university and the school. We could see that no changes occur through decrees, legal or institutional laws. For a real change, there should be a commitment of the educators, no matter if they are school trainers, biology teachers or members of the school boards.